PENGARUH PENGENCER SEMEN TERHADAP ABNORMALITAS DAN DAYA TAHAN HIDUP SPERMATOZOA KAMBING LOKAL PADA PENYIMPANAN SUHU 5ºC - Ridwan Ridwan (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The research objective was to determine the effects of semen diluter on the abnormality and survival of local goat spermatozoa maintained at 50C. The research used a Completely Randomized Design (CRD) of three different diluter (NaCl 0.9%, Lactate Ringer, and Dextrose Ringer) with six replicates. Analysis of variance showed that the treatment effects were highly significant (P<0.01)              on both the abnormality and survival of the goat spermatozoa. The spermatozoa abnormality was significantly higher in the lactate ringer treatment (6.26%) than any other treatment. Similarly,                  the survival of the goat spermatozoa in the dextrose ringer and NaCl treatment were significantly larger (77 and 80.5%) than that in the lactate ringer treatment (66,3%).